MODEL PENGEMBANGAN SDM INDUSTRI PERBANKAN SYARIAH PADA ISLAMIC BANKING SCHOOL YOGYAKARTA - Syaparudin Syaparudin (State Institute of Islamic Studies (IAIN) Salatiga, 2014)
This research aims to find out and to explore, describe, explain and map humanresources required by Islamic Banking Industry in Indonesia and the developmentof human resources in IBS Yogyakarta. This study is a field research using aqualitative approach. The design use qualitative descriptive design which issupported with interview, observation, documentation and library studies incollecting the datas. The datas which were collected, are analysed with descriptiveand content analysis. The result shows that human resources required by IslamicBanking Industry in Indonesia, are more than bankers. They have to own multidimension, competence with integrated sciences. To fulfill this, the developmentof human resources in IBS Yogyakarta is desiged with four main competences,so that they get ahead in entering the Islamic banking industry. The competenciesare: core competencies, behavior, functional and managerial competence.